Athletic performance optimization in hot environments - Mills, A. (Source Endurance, 2020)
What do the latest scientific studies say about heat adaptation? How can you prepare for a hot race if you don't live in a super hot environment? What is the role of electrolytes? How do you manage recovery from the heat during a stage race? All these and more questions answered Racing and Training in the Heat.